ANALYSIS OF SMK3 IMPLEMENTATION LEVEL AND ACCIDENT RISK IN THE ADMINISTRATION OFFICE BUILDING DEVELOPMENT PROJECT AT GUSTI NGURAH RAI AIRPORT BALI - I Ketut Sutapa; I Nyoman Ardika; I Nyoman Sutapa; I Nengah Darma Susila; I Putu Agus Krisnadinata (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
Every construction project, whether high-tech or simple, certainly has risks in its implementation process, therefore it is necessary to establish an Occupational Safety and Health Management System to minimize Occupational Safety and Health (K3) risks, but there are still many construction companies that are lacking in identifying K3 risks. and implementing an Occupational Health and Safety Management System (SMK3) in the process of implementing a construction project. The purpose of this study was to determine the level of OSH risk based on work items, as well as to measure the level of implementation of SMK3 in a construction project. In this research, the object of the case study is the construction project of the Administration Office Building at I Gusti Ngurah Rai Airport, Bali, during the lower structure work. After carrying out risk identification, 35 risk questions and 5 jobs are obtained, namely Borepile, Pilecap, Pendestal Column, Sloff, Roof Frame, then the results of the identification are processed and the risk level is obtained from the implementation of the Administration Office Building Construction Project at I Gusti Ngurah Rai Airport, Bali. Enter the Medium Category with a risk value of 8.69, while for the implementation of the Occupational Safety and Health Management System (SMK) the Administration Office Building Construction Project at I Gusti Ngurah Rai Airport, Bali is included in the good category with a total application value of 83%. Hopefully this research can become a reference in identifying K3 risks and a reference in implementing the Occupational Health and Safety Management System (SMK).